2014
DOI: 10.1111/ger.12126
|View full text |Cite
|
Sign up to set email alerts
|

Oral leiomyosarcoma: the importance of early diagnosis

Abstract: Early diagnosis and treatment play a key role in a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The differential diagnosis of malignant spindle cell tumors in the head and neck includes spindle cell carcinoma and melanoma; sarcomas to be distinguished include malignant nerve sheath tumor and rhabdomyosarcoma [14]. Due to overlap in histologic features, head and neck sarcomas [24] 35 F Buccal mucosa 1.0 × 1.0 n/r n/a n/a Suarez-Alen et al (2015) [25] 66 F Buccal mucosa 2.0 × 1.0 n/r Surgery 52-ANED Present case (2017) 87 M Buccal mucosa NR n/a n/a n/a may be misdiagnosed or misclassified by the pathologist; one review of head and neck soft tissue sarcomas revealed a change in diagnosis by the pathologist in 33-48% of the cases [10]. Given these difficulties, Dry et al pointed out that some of the previously reported cases that did not perform immunohistochemical studies, may in fact not be of myogenic origin [6].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of malignant spindle cell tumors in the head and neck includes spindle cell carcinoma and melanoma; sarcomas to be distinguished include malignant nerve sheath tumor and rhabdomyosarcoma [14]. Due to overlap in histologic features, head and neck sarcomas [24] 35 F Buccal mucosa 1.0 × 1.0 n/r n/a n/a Suarez-Alen et al (2015) [25] 66 F Buccal mucosa 2.0 × 1.0 n/r Surgery 52-ANED Present case (2017) 87 M Buccal mucosa NR n/a n/a n/a may be misdiagnosed or misclassified by the pathologist; one review of head and neck soft tissue sarcomas revealed a change in diagnosis by the pathologist in 33-48% of the cases [10]. Given these difficulties, Dry et al pointed out that some of the previously reported cases that did not perform immunohistochemical studies, may in fact not be of myogenic origin [6].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Besides early diagnosis, the prognosis of oral LMS patients depends on the tumour grade, size, site and treatment. [20][21][22] Currently, there are no standard criteria for therapy, although the complete excision of the tumour with wide surgical margins is recommended. 7,23,24 The five-year survival rate among patients with primary oral LMS is 55%, with bone involvement and metastasis significantly associated with poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to a 2007 study, the sites affected in the oral cavity, in decreasing frequency, are the maxilla and mandible, tongue, buccal mucosa, soft palate, upper lip, and floor of the mouth [10]. Jaw bones have been the most prevalent location for this tumor, accounting for 45% to 68% of the reported cases [3,5,11,12], with the second more frequent site being the tongue [9,11]. The least affected sites were the gingiva and upper lip [5].…”
mentioning
confidence: 99%
“…The clinical manifestation of oral LMS is usually that of a distinct, painless, circumscribed mass, which is firmly adhered to deeper planes, lacking specific symptoms that allow for its differentiation from other similar lesions [8,9]. There is no clear sex predilection, but it is noticeable that in the third and seventh decade, there were 50% more female than male patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation